Supervision of Management of Village Owned Enterprises (BUMDes) in Sidoarjo Regency - Gusti Ilman Akbar; Lailul Mursyidah (Indonesian Journal of Cultural and Community Development, 2022)
BUMDes is an institution or organization formed by the community and for the community without interference from the village government, therefore it is necessary for the management of the BUMDes to run optimally. The management of BUMDes in Trosobo Village, Taman District, Sidoarjo Regency is quite good because it already has a vision, mission, work program but there are still obstacles, namely lack of organization and lack of movement, direction in managing BUMDes in Trosobo Village. The method used in this study is a qualitative method. The results of the study indicate that the control or supervision of the management of BUMDes Trosobo has been going well because there are 3 supervisors who have been assigned to supervise and evaluate all ongoing BUMDes programs while this report is carried out every month which will then be held discussions about the ongoing BUMDes program. and not whether it has been maximized or not.